Skills shortages - will they derail the Australian Rail Transport Industry (ARTI)? - Mahendran, Anusha; Dockery, Alfred Michael (The Centre of Full Employment and Equity (CofFEE), 2008)
The prevalence of skills shortages in numerous sectors of the Australian economy has been a prominent topic of discussion in many circles including amongst various government, industry and employer groups, as well as the media. One industry where skills shortages have become a particular area of concern in recent times is in the Australian Rail Transport Industry (ARTI). Like other industries the ARTI experienced substantial rationalisation of its workforce during the 1990?s which resulted in considerable downsizing of employee numbers, reduced intake of young recruits and a significant decrease in training investment and skills development. The combined effect has left the ARTI facing several personnel problems including widespread labour shortfalls, an aging workforce and difficulties in relation to staff attraction and retention. Using information derived from the latest ABS Census statistics and primary data acquired from over twenty rail operators across Australia through questionnaires and in depth interviews, this paper builds on previous study findings to present a contemporary profile of the national rail workforce. This includes a current analysis of skills shortages and employment trends within the ARTI, along with a brief discussion of measures that are likely to assist in reducing the severity of the current skills crisis.